2021
DOI: 10.2174/1573403x17666210514005235
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Intermittent Hypoxia Conditioning as a New Rehabilitation/ Secondary Prevention Strategy for Patients with Cardiovascular Diseases: A Systematic Review and Meta-analysis

Abstract: Background: Once used by mountaineers to facilitate rapid adaptations to altitude and by athletes to improve their aerobic capacity, exposure to hypoxia has been proven to affect various physiological, clinically relevant parameters. A form of conditioning known as Intermittent Hypoxia Conditioning (IHC) consists of repeated exposures to intermittent hypoxia, combined with normoxia and hyperoxia, which has been shown to have potential as a treatment to improve cardio-metabolic risks profile in cardiac patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
1
2
1
1
Order By: Relevance
“…In this study, a 3-week IHHE course led to a significant decrease in SBP and DBP, with the blood pressure values in the IHHE group after the intervention being lower than in the control group despite being significantly higher initially. Similar hypotensive effects of an interval hypoxic-normoxic exposures course were noted by N.Lyamina [24], as well as in a recent systematic review which found a decrease in SBP by an average of 13.7 mmHg (p < 0.001), and DBP by 7.9 mmHg (p = 0.003) in patients with hypertension and coronary artery disease (CAD) after a course of hypoxic exposures [41]. This is corroborated by a N.Muangritdech et al [42] study showing a decrease in blood pressure and improvement of endothelial function/NO availibility in hypertensive patients both after a 6-week course of interval hypoxic-normoxic exposure at rest, and after a similar IHT course duration.…”
Section: Discussionsupporting
confidence: 71%
“…In this study, a 3-week IHHE course led to a significant decrease in SBP and DBP, with the blood pressure values in the IHHE group after the intervention being lower than in the control group despite being significantly higher initially. Similar hypotensive effects of an interval hypoxic-normoxic exposures course were noted by N.Lyamina [24], as well as in a recent systematic review which found a decrease in SBP by an average of 13.7 mmHg (p < 0.001), and DBP by 7.9 mmHg (p = 0.003) in patients with hypertension and coronary artery disease (CAD) after a course of hypoxic exposures [41]. This is corroborated by a N.Muangritdech et al [42] study showing a decrease in blood pressure and improvement of endothelial function/NO availibility in hypertensive patients both after a 6-week course of interval hypoxic-normoxic exposure at rest, and after a similar IHT course duration.…”
Section: Discussionsupporting
confidence: 71%
“…Overall, the results of this systematic review indicate that passive or active normobaric IH would have a limited positive effect on health-related outcomes in healthy older adults compared to similar intervention in normoxia, without any observed adverse effects in the participants. These findings differ from two recent reviews [ 48 , 49 ] indicating that intermittent hypoxia-hyperoxia protocols could be effective at the cardiovascular, metabolic, and cognitive levels in an elderly population suffering from various diseases. The free radical signaling during hypoxia-hyperoxia interventions may lead to better induction of antioxidant synthesis than IH only [ 25 ].…”
Section: Discussioncontrasting
confidence: 99%
“…These molecules are considered as profibrotic, proinflammatory, and likely heart and liver fibrosis markers (29). Therefore, their decrease may reflect a reduction in the chronic systemic inflammation typical in the patients with MS (3,30).…”
Section: Discussionmentioning
confidence: 99%